2020
DOI: 10.1093/aob/mcaa061
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded oligodeoxynucleotides induce plant defence in Arabidopsis thaliana

Abstract: Background and Aims Single-stranded DNA oligodeoxynucleotides (ssODNs) have been shown to elicit immune responses in mammals. In plants, RNA and genomic DNA can activate immunity, although the exact mechanism through which they are sensed is not clear. The aim of this work was to study the possible effect of ssODNs on plant immunity. Key Results The ssODNs IMT504 and 2006 increased protection against the pathogens Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
1
8
1
Order By: Relevance
“…Compared with the autotoxicity induced in plants by self-eDNA application previously ( Barbero et al, 2016 ; Duran-Flores and Heil, 2018 ; Serrano-Jamaica et al, 2020 ; Toum et al, 2020 ), it is noteworthy that self-eRNA-induced plant immunity was not accompanied by any growth penalty (also referred to as the allocation fitness cost; Figure 3 ). We cannot explain why allocation fitness cost is not required in the field trial of self-eRNA, but we have two hypotheses.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Compared with the autotoxicity induced in plants by self-eDNA application previously ( Barbero et al, 2016 ; Duran-Flores and Heil, 2018 ; Serrano-Jamaica et al, 2020 ; Toum et al, 2020 ), it is noteworthy that self-eRNA-induced plant immunity was not accompanied by any growth penalty (also referred to as the allocation fitness cost; Figure 3 ). We cannot explain why allocation fitness cost is not required in the field trial of self-eRNA, but we have two hypotheses.…”
Section: Discussionmentioning
confidence: 80%
“…Like DAMP signaling in animals, infiltration of Arabidopsis thaliana seedling leaves with single-stranded oligodeoxynucleotides (ssODNs) elicited defense response against Pseudomonas syringae pv. tomato ( Pto ) and Botrytis cinerea but not against Tobacco mosaic virus and inhibited growth via the BAK co-receptor and ROS generation ( Toum et al, 2020 ). Besides plant self-eDNAs, a mixture of fragmented 100 μg/ml non-self-eDNAs derived from plant pathogenic fungi including Phytophthora capsici, Fusarium oxysporum, and Rhizoctonia solani reduced the mortality of pepper ( Capsicum annuum L.) plants by up to 40% ( Serrano-Jamaica et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the appearance of the DNA damage marker γ-H2A.X as soon as 2 h after pathogen infection (much earlier than the first observable signs of plant cell death; Zhang et al, 2004;Song et al, 2015) suggest DNA damage may not just be an indirect product of the plant hypersensitive response. Indeed, damaged DNA (both foreign and host) has been reported to potentiate immune responses (Wen et al, 2009;Yakushiji et al, 2009;Gallucci and Maffei, 2017;Toum et al, 2020). Finally, the ability of DNA damaging treatments to promote innate immunity (Kunz et al, 2008;Yan et al, 2013) also suggests DNA damage and its consequent response pathways may activate immune signaling in plants.…”
Section: Discussionmentioning
confidence: 99%
“…To determine importance of CpG motifs ( 23 ), the ODNs IMT504 (5’-CATCATTTTGTCATTTTGTCATT-3’) and 2006 (5’- TCGTCGTTTTGTCGTTTTGT-3’) and their complementary sequences (IMT504c: 5’- AATGACAAAATGACAAAATGATG-3’; 2006c: 5’-ACAAAACGACAAAACGACGA-3’) were purchased from Sigma Aldrich and used as single stranded DNA (ssDNA). To generate double stranded DNA (dsDNA), each ODN was annealed with its complementary sequence in a C1000 Thermal cycler (Biorad) by heating to 95°C for 3 minutes and cooling to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Treatments with plant DNA, genomic or plasmid bacterial DNA, or synthetic single stranded oligodeoxynucleotides (ssODNs), were shown to trigger early immune responses that are highly conserved between plants and mammals, including Ca 2+ fluxes, membrane depolarization, the formation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ), or the activation of mitogen-activated protein kinases (MAPKs) ( 9 , 20 22 , 25 , 27 , 34 , 35 ). The responses include massive transcriptomic reprogramming ( 24 , 25 , 35 ), and studies at the phenotypic level reported not only increased immunity (‘resistance’) to microbial pathogens, but also increased ‘defence’ to plant-specific pests such as leaf and sap-sucking herbivores ( 21 , 23 , 26 , 27 , 29 , 33 36 ). Strikingly, stronger responses to self- in comparison to nonself-DNA were reported in most, although not all, of the studies that compared DNA from different sources.…”
Section: Introductionmentioning
confidence: 99%